Enhanced perceptual functioning in autism: an update, and eight principles of autistic perception. - Mottron L; Dawson M; Soulières I; Hubert B; Burack J (Journal of Autism & Developmental Disorders, 2006)
We propose an 'Enhanced Perceptual Functioning' model encompassing the main differences between autistic and non-autistic social and non-social perceptual processing: locally oriented visual and auditory perception, enhanced low-level discrimination, use of a more posterior network in 'complex' visual tasks, enhanced perception of first order static stimuli, diminished perception of complex movement, autonomy of low-level information processing toward higher-order operations, and differential relation between perception and general intelligence. Increased perceptual expertise may be implicated in the choice of special ability in savant autistics, and in the variability of apparent presentations within PDD (autism with and without typical speech, Asperger syndrome) in non-savant autistics. The overfunctioning of brain regions typically involved in primary perceptual functions may explain the autistic perceptual endophenotype.